2016
DOI: 10.1093/mnras/stw1106
|View full text |Cite
|
Sign up to set email alerts
|

The conjectured S-type retrograde planet in ν Octantis: more evidence including four years of iodine-cell radial velocities

Abstract: Released ABSTRACTWe report 1212 radial-velocity (RV) measurements obtained in the years 2009-2013 using an iodine cell for the spectroscopic binary ν Octantis (K1III/IV). This system (a bin ∼ 2.6 au, P ∼ 1050 days) is conjectured to have a Jovian planet with a semi-major axis half that of the binary host. The extreme geometry only permits long-term stability if the planet is in a retrograde orbit. Whilst the reality of the planet (P ∼ 415 days) remains uncertain, other scenarios (stellar variability or apsidal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 86 publications
(162 reference statements)
0
14
0
Order By: Relevance
“…Planets in S-type orbits around tight binaries with periastron distances less than 10 au have also been reported around KOI-1257 (Santerne et al 2014), Kepler-444 (Dupuy et al 2016), HD 59686 (Ortiz et al 2016), and possibly ν Octantis (Ramm et al 2016). If confirmed to be a low-mass star, Kepler-693c has the smallest peristron among such stellar companions.…”
Section: Implications For the In Situ Formation Scenariomentioning
confidence: 80%
“…Planets in S-type orbits around tight binaries with periastron distances less than 10 au have also been reported around KOI-1257 (Santerne et al 2014), Kepler-444 (Dupuy et al 2016), HD 59686 (Ortiz et al 2016), and possibly ν Octantis (Ramm et al 2016). If confirmed to be a low-mass star, Kepler-693c has the smallest peristron among such stellar companions.…”
Section: Implications For the In Situ Formation Scenariomentioning
confidence: 80%
“…This result is not unexpected -such retrograde solutions are almost always highly stable unless they feature mutually crossing orbits (e.g. Eberle & Cuntz 2010;Horner et al 2011Horner et al , 2012bWittenmyer et al 2013a,b;Ramm et al 2016).…”
Section: The Stability Of the Bouchy And Campanella Solutionsmentioning
confidence: 88%
“…In Morais & Correia (2012) the authors develop a secular theory for such systems and derive an expression for the precession rate of the orbit of the companion pair around the main component. Furthermore they suggest this effect as an alternative explanation to the planet hypothesis for the ν Octantis system (Ramm et al 2009(Ramm et al , 2016, which is known to be a close single-line spectroscopic binary where the two stellar components orbit each other with a period of 1050 d. In addition to the long-period RV signal caused by the stellar companion, Ramm et al (2009) observed short-period RV variations with a period of 417 d, which they interpreted as a possible planet with a minimum mass of 2.5 M jup . Stable orbital configurations have been published by Ramm et al (2016), but previously the stability of the proposed planet seemed questionable.…”
Section: Hierarchical Triplementioning
confidence: 93%